2018
DOI: 10.1039/c8nr02347f
|View full text |Cite
|
Sign up to set email alerts
|

Towards molecular electronic devices based on ‘all-carbon’ wires

Abstract: Nascent molecular electronic devices based on linear 'all-carbon' wires attached to gold electrodes through robust and reliable C-Au contacts are prepared via efficient in situ sequential cleavage of trimethylsilyl end groups from an oligoyne, MeSi-(C[triple bond, length as m-dash]C)-SiMe (1). In the first stage of the fabrication process, removal of one trimethylsilyl (TMS) group in the presence of a gold substrate, which ultimately serves as the bottom electrode, using a stoichiometric fluoride-driven proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 94 publications
(45 reference statements)
0
31
0
Order By: Relevance
“…In addition to building blocks, “wires” must also be considered in the design of molecular electronic devices. The desirable properties of conjugated carbon “linkages,” for example, ─CC─, as wires between building blocks have prompted a huge and diverse body of research in polyenes, cumulenes, and related molecular motifs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to building blocks, “wires” must also be considered in the design of molecular electronic devices. The desirable properties of conjugated carbon “linkages,” for example, ─CC─, as wires between building blocks have prompted a huge and diverse body of research in polyenes, cumulenes, and related molecular motifs …”
Section: Introductionmentioning
confidence: 99%
“…The desirable properties of conjugated carbon "linkages," for example, ─C C─, as wires between building blocks have prompted a huge and diverse body of research in polyenes, cumulenes, and related molecular motifs. [20][21][22][23][24][25] In this investigation we will use next-generation QTAIM that includes a 3-D, non-minimal three-stranded directional interpretation of bonding, incorporating the most preferred direction of electronic charge density accumulation using ethene as the molecular wire. [26] This directional approach can be used in a variety of circumstances where conventional QTAIM, [27] that only provides scalar measures such as bond ellipticity ε, is not useful.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The promise of such properties has piqued the interest of abroad range of materials,p olymer and theoretical chemists but has also naturally attracted the attention of synthetic chemists,in particular in the field of organometallic chemistry, [4] not only inspired by the fundamental synthetic challenges,but also for the possibility that molecular electronic or electro-optical applications might emerge,a nd the raft of spectroscopic techniques that may be brought to bear on interrogating the properties of molecular model compounds. [5] Terminating poly-yne chains with bulky end-caps has been shown to confer stability allowing discreet sp-carbon chains as long as Tr *-(C C) 22 -Tr* (Tr* = tris(3,5-di-t-butylphenyl)methyl) to be isolated, [6] whilst in the transition metal regime,the longest chain achieved to date is found in Gladyszsc omplex [Pt 2 -(m-C 28 )R 2 (PR 3 ) 4 ]( R = C 6 H 4 Me-4). [7] These poly(carbyne) mimics all have in common that the chain is terminated by single metal-carbon bonds,i .e., they may be described as poly-yn-diyls (Scheme 1a).…”
Section: In1885mentioning
confidence: 99%
“…Moreover, a recent contribution has revealed that SAMs prepared from the solution deposition of dithiols do not have a chemisorbed character [181]. For these reasons, many other anchor groups have been studied in the last two decades on different substrates (SiO 2 , Cu, Ag, Au, WO 3 , and ITO-indium tin oxide-among others), including selenols [94], amines [110,111], cyanides and isocyanides [95,96], isothiocyanates [182], trimethylsilyl group [183,184], acetylenes [107,112,124,185], thiophenes [132,186], trichlorosilanes [133], trimethoxysilanes [97,142], phosphonate [98,105] terminated molecules, perylenes [187], and fullerenes [106,188,189]. Recently, Qiu et al [106] reported the spontaneous formation of molecular junctions of glycol ether functionalized fullerenes on Au TS , which resulted in the large stability and robustness of the SAMs.…”
mentioning
confidence: 99%
“…Self-assembly strategies in which molecules are located onto a gold electrode by forming covalent Au-C σ-bonds [208] have resulted in SAMs with a significantly higher conductance than those with the above-described conventional anchoring groups [76,[209][210][211]; electrically transmissive monolayers with Au-C junctions have also been reported [112]. These results are attributable to the creation of exceptionally stable SAMs (~4 eV) and strong electronic coupling because of an uninterrupted conjugation between the electrode and the molecule [107,212]. These investigations have been extended to other interfaces, including various metal-C and C (from the electrode)-C (from the molecule) [212], as well as silicon-C junctions [34].…”
mentioning
confidence: 99%